Self-managing teams : creating and maintaining self-managed work groups - Hicks, Robert (Crisp Pub. Menlo ParkUS, 1990)
Explains what self-managing teams (SMTs) are, and how to determine whether an organization is ready for them. Teaches how to establish and maintain an SMT programme and shows how organizations and employees benefit from SMT programmes.